THE EFFECT OF COMMODITY EXPORTS AND FOREIGN DEBT ON FLUCTUATIONS OF INDONESIA'S FOREIGN EXCHANGE RESERVES - Noviami Trisniarti; Mutia Rahmah; Muhammad Hafizh; Andika Al Imran; Anggi Rahayu (RADJA PUBLIKA, 2024)
Foreign exchange reserves are crucial in maintaining macroeconomic stability, particularly in developing countries. This study aims to analyze the impact of commodity exports and external debt on Indonesia's foreign exchange reserves from 1990 to 2023. A quantitative approach with a multiple linear regression model was employed, using time-series data sourced from BPS, the World Bank, and Bank Indonesia. The dependent variable is foreign exchange reserves, while the independent variables include CPO exports, metal exports, and external debt. The findings indicate that CPO exports significantly improve foreign exchange reserves, highlighting their strategic importance as a primary export commodity. In contrast, metal exports show a significant negative impact, driven by low value-added processing and high dependency on imported materials. External debt demonstrates positive and significant effects, reflecting its utility in strengthening reserves when effectively managed. This study emphasizes the need to enhance value-added processes for commodity exports and prudently manage external debt to optimize Indonesia's foreign exchange reserves. Future research could explore other variables, such as foreign direct investment (FDI), monetary factors, tourism, or labour, to provide deeper insights and refine analytical tools.